Serology and Virulence of Xanthomonas campestris pv. manihotis Strains in Thailand - Chalida Leksomboon; Niphone Thaveechai; Wichai Kositratana; Ampaiwan Paradornuwat; Chareinsuk Rojanaridpiched (Agriculture and Natural Resources, 1992)
Serological relationship among 13 strains of Xanthomonas campestris pv. manihotis (Xcm) in Thailand was determined by four serological methods of Ouchterlony double diffusion test (ODD), indirect immunofluorescent staining (IF), enzyme-linked immunosorbent assay (ELISA) and dot-immunobinding assay (DIBA) using antiserum to membrane protein complex (MPC) of Xcm strain CBa. All 13 strains of Xcm were not serologically different by the four tested methods. For specificity of MPC antiserum, ODD test was highly specific to Xcm stains and no cross-reaction with 16 other bacteria. However, IF, ELISA and DIBA methods were not distinguished Xcm strains from X. campestris pv. citri. Although IF test was the most sensitive method since it could detect Xcm at 102 cfu/ml, however DIBA was considered the most suitable method of detection because it was simple, rapid and required inexpensive equipment. Study on virulence of 13 strains of Xcm on cassava var. Rayong 1 demonstrated variable disease reactions that can be categorized into three groups of high, medium and low virulent strain. There was no correlation between virulence and source (geographical distribution) of pathogen.